Partisipasi Perempuan dalam Aktivitas Pariwisata: Studi Kasus Suku Baduy - Rina Fitriana; Dadan Sujana; Dino Gustaf Leonandri (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2020)
This research aims to analyze women’s participation in tourism activities in the Outer Baduy tribe, according to the tourism components consisting of attraction, amenity, accessibility, and ancillary (supporting factors). This research uses a qualitative research method, in which data collected through interviews, observations, and documentation. This research involved 18 informants from several stakeholders, such as the tourism awareness group, handicraft producers, homestay and restaurant owners, government officers, and tourists who have visited the destination. Informants’ selection uses a purposive sampling technique. According to the tourism components, the research results show women’s participation in tourism activities in the Outer Baduy tribe, only two of four tourism components: attraction and amenity. In the attraction component, women possess more or less the same level of participation as men. However, in the amenity component, women may have a higher level of participation than men may. In the accessibility and ancillary (supporting factors) components, only men participation existed. The limited level of women’s participation is rooted deep and taken for granted in their culture. The women themselves do not dispute inequality and disparity because they consider their role as women in the domestic sector and not in the public sector.